Knowledge, Attitude and Perception of Undergraduate Medical Students on Medico-Legal Autopsies - Tarafder, Aditi; Zahan, Md Sarwar; Hasan, Md Khalid Ibn; Sunny, Sonia Naznin; Simi, Tamanna Hossain; Roy, Milon; Sporshow, Shifat Jannat; Rahman, Md Jahidur; Akter, Fajana; Debnath, Milton Kumar; Sultan, Mohammad Tipu (Community Based Medical Journal, 2026)
A descriptive, cross-sectional study was conducted in the Department of Forensic Medicine, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from September 2023 to February 2025, to evaluate the knowledge, attitudes, and perceptions of undergraduate medical students regarding medico-legal autopsies, exploring the impact of forensic medicine education on their understanding and appreciation of autopsies in future medical practices. A total of 105 students from third to fifth year of the MBBS program were selected through convenient sampling. Before data collection consent was taken and confidentiality was strictly maintained. Data was collected through a semi-structured, pre-tested questionnaire. The mean age of participants was 22.26±1.12 years, with most in the 21–22 years age group (68.6%). Gender distribution was nearly balanced (51.4% male and 48.6% female). A significant portion of respondents (73.3%) demonstrated knowledge of the purpose of autopsies, while 88.6% recognized the necessity of postmortem examinations in all unnatural deaths (P<0.001). 73.3% students know the aims of autopsy which is to determination of cause and circumstance of death. 35.2% students think that autopsy is indicated in suicidal death. 84.8% of students have an idea about the laboratory for chemical analysis but they have (69.5%) wrong idea about the preservatives of viscera which they think is formalin. 63.8% of students have knowledge that stomach, liver and kidney are preserved for chemical analysis (P<0.001). 79% of students recognize that an inquest report is necessary before conductive medico-legal autopsy. 78.1% know the classification of postmortem and they (67.6%) also know that virtual autopsy new form of postmortem examination. Comfort with autopsy exposure was reported by 75.2% of students, 97% students do not think autopsy as a harassment to the victim’s family and 78% endorsed the inclusion of autopsies in the curriculum. 67.6% strongly agreed that autopsy helped in improving students anatomy. However, 80% expressed dissatisfaction with the limited number of autopsies observed (P<0.001). Overall, undergraduate medical students exhibit positive attitudes and awareness towards medico-legal autopsies; however, some gaps in practical exposure/training and emotional preparedness were identified by them. CBMJ 2026 January: vol. 15 no. 01 P:224- 232